Realidade aumentada, capital cultural e turismo literário: Aplicação a um Percurso Camiliano. - Liliana Félix Leite (2017)
This paper presents an ongoing research project on the relationships among capital cultural, digital literacy and digital participation related with an exploration of a literary trail based on Camilo Castelo Branco's experiences at Oporto city. The literary trail will use mobile devices with access to Internet, augmented reality (aurasma) and geolocalization. It is expected that the very own participants had access to the augmented reality pieces in the city, and comment on them at a website that incorporate the project. Based on a convenience sample, we will use a mixed-methods approach supported by questionnaires, observation, interviews and analysis of the digital participations of the participants in the website.